Virtual engineering of cyber-physical automation systems: The case of control logic. (January 2019) - Schneider, Georg Ferdinand; Wicaksono, Hendro; Ovtcharova, Jivka
Highlights: Support for the simultaneous engineering of the cyber and the physical part of CPS. Extension of life cycle centered view of conceptual architectures with iterative method. Integration with life cycle centered view mandated by digital twin paradigm. Modular ontology for both the cyber and physical part of an industrial automation system. Automated verification of different control logic types. Simultaneous verification of cyber and physical parts of CPS. Abstract: Mastering the fusion of information and communication technologies with physical systems to cyber-physical automation systems is of main concern to engineers in the industrial automation domain. The engineering of these systems is challenging as their distributed nature and the heterogeneity of stakeholders and tools involved in their engineering contradict the need for the simultaneous engineering of their cyber and physical parts over their life cycle. This paper presents a novel approach based on the virtual engineering method, which provides support for the simultaneous engineering of the cyber and physical parts of automation systems. The approach extends and integrates the life cycle centered view mandated by current conceptual architectures and the digital twin paradigm with an integrated, iterative engineering method. The benefits of the approach are highlighted in a case study related to the engineering of the control logic of a cyber physical automation system originating from the process engineering domain. We describe for the first time a modular domain ontology, which formally describes the cyber and physical part of the system. We present cyber services built on top of the ontology layer, which allow to automatically verify different control logic types and simultaneously verify cyber and physical parts of the system in an incremental manner.